Tutorial review: Simultaneous measurement of particle size and particle charge - Brown, R.C (Journal of aerosol science, 1997)
Simultaneous measurement of particle size and charge usually involves a conventional method for the former, which is compatible with a chosen method for the latter. Measurements of charge are of two types: static, in which the absolute charge is measured; and dynamic, in which the electrical mobility is measured. Static measurements rely on charge transfer or induction using a complete or incomplete Faraday cage. They tend to be limited to particles of high charge or aerosols that have unipolar charge. Dynamic methods usually involve subjecting the aerosol to a high electric field, measuring or inferring the velocity that the particle reaches and relating this to the electrical mobility. The charge on small particles can easily be measured in this way, but the drawback so far as population measurements are concerned is that the requirement for details of both size and charge necessitates a large number of “bins” and, therefore, a long sampling time. Means of coping with the problems that this causes are discussed, and the method in which a particle is made to respond to a temporally varying electric field is also described. No method is without complications or practical problems, and the need for further work on the subject is apparent.